Depression and Posttraumatic Stress Disorder in Temporary Settlement Residents 1 Year After the Sichuan Earthquake. (March 2015) - Cheng, Zhang; Ma, Ning; Yang, Lei; Agho, Kingsley; Stevens, Garry; Raphael, Beverley; Cui, Lijun; Liu, Yongqiao; Yan, Baoping; Ma, Hong; Yu, Xin
The authors sought to determine the prevalence and risk factors for major depressive disorder and posttraumatic stress disorder (PTSD) among survivors living in temporary accommodation in the Yongxing settlement in Mianyang city 1 year after the Sichuan earthquake for further interventions. They interviewed 182 residents, using the Structured Clinical Interview for DSM-IV Axis I Disorders and a self-report questionnaire. The 12-month prevalence of depressive disorder and PTSD were 48.9% and 39.6%, respectively. Multivariate analysis indicated that bereaved survivors were 5.51 times (adjusted odds ratio [AOR] = 5.51; 95% confidence interval [CI] =2.14-14.22) more likely to report PTSD and 2.42 times (AOR = 2.42; 95%CI =1.00-5.48) more likely to report depressive disorder than nonbereaved survivors. Older age and receipt of government financial support were significantly associated with 12-month PTSD. Depressive disorder 12 months after the earthquake was associated with receipt of government financial support, pre-earthquake physical illness, single marital status, being currently employed, and Han ethnicity